FORMATION OF ХХІ-ST CENTURY SKILLS IN SECONDARY AND SPECIALIZED EDUCATION STUDENTS USING DIGITAL TOOLS - Yaremiy, Sofiya; Vlasiy, Olesya; Yaremiy, Ivan (Physical and Mathematical Education, 2025)
Formulation of the problem. The current issue in education is the rethinking of digital technology usage, not only as technical tools for learning but also as means to foster 21st-century skills. The diversity of digital services offers an endless variety of approaches to their application. Therefore, this article focuses on digital tools such as office suites, virtual laboratories, open data services, cloud technologies, and artificial intelligence to develop 21st-century skills in secondary and specialized education students while studying informatics disciplines.Materials and methods. The study used a range of methods, including theoretical research methods (analysis, generalization, explanation, classification, comparison, generalization of pedagogical experience) and empirical research methods (description, observation, questionnaires and surveys, experiment, statistical analysis). The pedagogical experiment was conducted on the basis of the Professional Medical College of Ivano-Frankivsk National Medical University in the academic year 2023-2024. 60 second-year students studying under the educational and professional program "Prosthetic Dentistry" took part.Results. The materials developed in the course of the study were implemented in the process of studying the discipline "Fundamentals of Medical Informatics". On their basis, the impact of integrating digital technologies into educational courses (on the example of the discipline "Fundamentals of Medical Informatics") on the development of students' skills of the XXI century was analyzed. The pedagogical experiment showed that the use of the above digital tools increases student motivation and performance compared to traditional methods.Conclusions. Using digital tools expands the possibilities for building 21st-century skills, particularly developing digital skills to solve complex problems and promoting critical thinking and creativity. Integrating project-based courses into the educational process promotes teamwork, leadership skills, and practical application of knowledge.
Keywords: digital tools; 21st-century skills; Microsoft Office suite; pedagogical experiment; project-based learning; critical thinking; creativity; digital literacy